Competition and Merit Order Effect in the Colombian Electricity Market - Perez, Alex; Carabali, Jaime; Benavides-Franco, Julian (International Journal of Energy Economics and Policy, 2022)
In this paper, we study the relationship between the merit order effect and the ownership structure of renewable resources in electricity markets. We use daily frequency data from the Colombian electricity market in 2012-2019 and designed a strategy to estimate the spot price’s dependence on renewable energy. We study how the participation of multi-technology firms in renewable energy alters the spot price. Our main results show a merit order effect for the Colombian electricity market, but this weakens in the presence of greater participation of multi-technology firms in the total availability of renewable energy for the day.